Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Studi Kasus THRIFT MEGA STORE Sumberjo, Kota Batu) - Salma Sundya Retha; Eka Farida; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of quality product, price, and quality service on purchase decision at THRIFT MEGA STORE. The research used is a quantitative method. The population in this consumers for all groups in the THRIFT MEGA STORE, as many 115 consumers. While the sample used in this consumer were 100 samples. The data used is primary data using a questionnaire. The data analysis method used is instrument test: validity and reliability test, normality test, classic assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the results of the study simultaneously obtained results that product quality, price and service quality have a significant effect on purchasing decisions, product quality variables have a not significant positive effect on purchasing decisions, price variables have a significant positive effect on purchasing decisions and service quality variables have a significant positive effect on purchasing decisions .  Keywords: Quality of Product, price, quality of service, purchase decision